Country-of-origin and customer purchasing decision - Vanoverbeke, Audrey Monique Pascale (2021)
2020 was a year of many challenges in business world from presidential elections, Covid-19 crisis to the moral conflict between Turkey and EU. Those crises differ in nature but led many individuals to question the importance of national industries and supply chain. Country-of-origin effect (to be called COO) argues that some factors are operating at the individual consumer’s psychological level when it comes to purchase a product, or judge someone. Stereotypes have a lot to play in this concept and will be looked at when it comes to understand the roots or this psychological bias. This paper addresses the concept and the roots of the country-of-origin effect, then will look at the concept of customer purchasing decision and how it can be influenced by the COO. This study will be conducted with concerns for the food industry as it has become a hot topic for managers in this sector. In addition to narrowing on the food industry, this paper will try to demonstrate that generational segmentation is to consider when looking at that impact COO has on purchasing decision. To do so we will be launching a questionnaire so to gather data regarding people purchasing behaviour in the light of country-of-origin. This paper found out that even though COO is one of the major factor people consider when buying food related goods, the impact of COO effect differs depending on generations individuals belong to and the region the food-related good originates from.